Optimizing HIV testing services in sub‐Saharan Africa: cost and performance of verification testing with HIV self‐tests and tests for triage. (25th March 2019) - Eaton, Jeffrey W; Terris‐Prestholt, Fern; Cambiano, Valentina; Sands, Anita; Baggaley, Rachel C; Hatzold, Karin; Corbett, Elizabeth L; Kalua, Thoko; Jahn, Andreas; Johnson, Cheryl C
Abstract: Introduction: Strategies employing a single rapid diagnostic test (RDT) such as HIV self‐testing (HIVST) or "test for triage" (T4T) are proposed to increase HIV testing programme impact. Current guidelines recommend serial testing with two or three RDTs for HIV diagnosis, followed by retesting with the same algorithm to verify HIV‐positive status before anti‐retroviral therapy (ART) initiation. We investigated whether clients presenting to HIV testing services (HTS) following a single reactive RDT must undergo the diagnostic algorithm twice to diagnose and verify HIV‐positive status, or whether a diagnosis with the setting‐specific algorithm is adequate for ART initiation. Methods: We calculated (1) expected number of false‐positive (FP) misclassifications per 10, 000 HIV negative persons tested, (2) positive predictive value (PPV) of the overall HIV testing strategy compared to the WHO recommended PPV ≥99%, and (3) expected cost per FP misclassified person identified by additional verification testing in a typical low‐/middle‐income setting, compared to the expected lifetime ART cost of 3000. Scenarios considered were as follows: 10% prevalence using two serial RDTs for diagnosis, 1% prevalence using three serial RDTs, and calibration using programmatic data from Malawi in 2017 where the proportion of people testing HIV positive in facilities was 4%. Results: In the 10% HIV prevalence setting with a triage test, the expected number of FP misclassifications was 0.86 per 10, 000 tested without verification testing and the PPV was 99.9%. In the 1% prevalence setting, expected FP misclassifications were 0.19 with 99.8% PPV, and in the Malawi 2017 calibrated setting the expected misclassifications were 0.08 with 99.98% PPV. The cost per FP identified by verification testing was 5879, 3770, and 24, 259 respectively. Results were sensitive to assumptions about accuracy of self‐reported reactive results and whether reactive triage test results influenced biased interpretation of subsequent RDT results by the HTS provider. Conclusions: Diagnosis with the full algorithm following presentation with a reactive triage test is expected to achieve PPV above the 99% threshold. Continuing verification testing prior to ART initiation remains recommended, but HIV testing strategies involving HIVST and T4T may provide opportunities to maintain quality while increasing efficiency as part of broader restructuring of HIV testing service delivery.